Digitalisasi Kaligrafi Arab Melalui Aplikasi Anā Muhtārif Āl-Khāt - Dina Nurul Arofah; Ikhwan Nur Rois (Tifani : Jurnal Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Arabic has a characteristic in its writing which is known as Arabic calligraphy (khāt). Calligraphy is the art of writing in Arabic, so it requires a medium or writing tool. This type of research is a qualitative research using a descriptive approach. Anā Muhtārif āl-Khāt is a tool that helps improve one's ability to write in Arabic. Anā Muhtārif āl-Khāt is a solution in the form of digitizing Arabic calligraphy. The results of this study are in the form of an explanation related to calligraphy, types of khāt, khāt expert figures and the process of making Arabic calligraphy with the Anā Muhtārif āl-Khāt application.